Influence of Advertising on Platform YouTube on Interest in Buying Netflix Services Products - Aryadi, Muhammad Alfian; Safitri, Dini; Putri , Kinkin Yuliaty Subarsa (Tecno Scientifica Publishing, 2024)
The development towards digital has made many changes that have occurred in various aspects of human life. In this era, many social media applications have sprung up which are certainly a means of entertainment for some people. With the increasing frequency of access to social media, several product or service companies advertise their products or services on social media, one of which is Netflix. One of the social media that they use to advertise their services is Youtube. This is becausee YouTube has become one of the most frequently accessed social media by people. This study uses a quantitative method with a correlational approach. The population contained in this study were 82 students of the Communication Science study program, Universitas Negeri Jakarta, 2019. Sampling in the study using probability sampling method by means of simple random sampling. The number of sample taken was 68 respondents based on calculations using the Slovin formula. From this study, the results obtained are that there iss an influence between ads on Youtube platform on students buying interest. This is evidenced by calculations using t count and t table and significance analysis. In addition, Netflix advertisements on Youtube have a direct relationship with the variable Y with a constant value of 4.228. Therefore, it can be ignored that Ads on Youtube Platform have an influence on the interest in buying Netflix service products.